Special topics in education, volume 3 - Dayagbil, Filomina T.; De Leon-Abao, Ethel; Lapingcao, Nenita V.; Polinar, Deletah DG.; Laplap, Floriza N.; Villareal, Noemi M.; Borabo, Heidi Grace L.; Inocian, Reynaldo B.; Ilvido, Michelle Mae J (Cubao, Quezon City : Lorimar Publishing, 2012)
These modules on Special Topic in Education are PAFTE's response to the need for instructional material for the three-unit professional education course in Special Topics. It is a compilation of at least ten (10) Modules written by members of PAFTE all over the country for PAFTE members most especially and also for non- PAFTE members. The teacher education curriculum includes a three-unit course on Special Topics to give every teacher education institution an opportunity to select current issues and topics not included in the other professional education courses but are seen to be important and highly relevant to its mission vision. The course on Special Topic likewise gives the teacher education student an opportunity to explore topics and issues related to his/ her field of study.
A Teacher for the World: Are You In?/ Filomena T. Dayagbil 1 -- Critical Thinking : The Power to Think Beyond Borders/ Ethel D. Abao 7 -- Alternative Learning System Beyond Borders/ Nenita V. Lapingcao 14 -- Research Exposure: A Teacher's Edge in 21st Century/ Floriza N. Laplap34 -- Information Literacy: The Defining Paradigm of Modern Education/ Noemi M. Villareal 43 -- Storytelling: What Makes an Effective Storyteller/ Heidi Grace L. Borabo 54 -- Peace Education in the Workplace vis-a-vis The Teacher's Role / Reynaldo B. Inocian 63 -- The Teacher as an Effective Stress Manager/ MichelleMae J. Olvido 72 -- The Classroom as a Global Community/ Noemi M. Villareal 81
Includes bibliographical references.
Keywords: EDUCATION -- PHILIPPINES